Tata Letak Dan Pengelolaan Gudang PT. Distribusi Prima - Az Zahra, Fatimah; Fikri, T. Muhammad Jibran; Simanjutak, Sanjaya; Musyarofah, Nadya Tari (Publika Bersama Nusantara, 2025)
This study aims to analyze and optimize the warehouse layout of PT. Distribusi Prima, a distribution company facing challenges in efficient warehouse management. Covering 600 m², the warehouse is divided into storage, receiving, and shipping areas. A case study approach was used, with ABC Analysis to categorize items based on demand frequency: beverages (high), home electronics (medium), and books & stationery (low). The layout adopts an I-Shaped Flow Warehouse concept and is visualized in 2D and 3D designs using SmartDraw and Rayon Design. Results show that item placement is suboptimal, leading to delays, inefficient forklift movement, and recording errors. Recommendations include optimizing forklift paths, implementing a Warehouse Management System (WMS), using barcode technology, applying the FIFO system, and improving employee facilities and safety. The redesigned layout is expected to streamline distribution flow, maximize storage capacity, and enhance operational efficiency and customer satisfaction. This research provides practical and academic contributions to warehouse management through data-driven strategies and adaptive workflow efficiency in the distribution industry.